Analisis Spasial Pengembangan Kawasan Wisata Air Terjun Andawe di Desa Matahori, Kecamatan Padangguni, Kabupaten Konawe - Taufik; Husain, Osu Oheoputra; Mukaddas, Jamal; Arfah, Jabal (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Spatial analysis of the research on the development of the tourism area in Andawe waterfall at Matahori village aims to determine the direction of the use of space in the tourism area. Based on the administrative location, it is around a forested area, so guidance is needed regarding the ability of the land around the tourism area to remain everlasting and sustainable. The method used spatial overlay analysis based on geographic conditions, including land usage, slope, soil type, and rainfall in Matahori Village. Based on the results of determining the geographical conditions, a quantitative analysis used the scoring method to determine the development potential of the land in the tourist area of ​​the Andawe waterfall. According to the study’s results, the tourism area of ​​the Andawe waterfall has a high and bit high level of land development opportunities. Facilities and infrastructure can be built to support tourism activities when land development opportunities are high. Meanwhile, a sufficiently high-level development of land management is required to protect and preserve natural resources. The direction of the tourism development concept at the Andawe waterfall is more recommended for the development of joint tourism